Keterampilan Membaca Bahasa Arab dalam Pendekatan Metakognitif - Tania, Elis; Isnaini, Rohmatun Lukluk (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2023)
Abstract: Purpose- This study aims to analyze the use of a metacognitive approach in developing Arabic reading skills. The metacognitive approach refers to students' understanding and self-regulation of their learning process, including understanding reading strategies, monitoring comprehension, and reflecting on the understanding they have acquired. Design/Methodology/Approach- This study uses the library research method, in which researchers collect data from scientific articles and books that are relevant to the research topic. The data obtained was then analyzed using content analysis techniques (Content Analysis), in which the researcher identified themes and patterns in the collected data. Findings- The discussion of this research is focused on the application of a metacognitive approach in developing Arabic reading skills. The results of this study can provide insight into the effective use of a metacognitive approach in improving Arabic reading skills and can become the basis for developing more effective curricula and learning methods. Research Limitation/Implications- This research is still theoretical without any field tests as a comparison instrument. However, this research can be the first step in assessing and evaluating this approach, whether it is based on the scientific hypothesis of experienced Arabic learning experts or not.